Epigenetics and Gut Microbiota in the Pathogenesis and Treatment of Bipolar Disorder (BD) - Shabnam Nohesara; Hamid Mostafavi Abdolmaleky; Ahmad Pirani; Sam Thiagalingam (Cells)
Bipolar disorder (BD) is a multifactorial mental disease with a prevalence of 1–5% in adults, caused by complex interactions between genetic and environmental factors. Environmental factors contribute to gene expression alterations through epigenetic mechanisms without changing the underlying DNA sequences. Interactions between the gut microbiota (GM) and diverse external factors, such as nutritional composition, may induce epigenetic alterations and increase susceptibility to BD. While epigenetic mechanisms are involved in both the pathogenesis of BD and drug treatment responses, epigenetic marks could be employed as predictors and indicators of drug response. This review highlights recent studies on the potential role of epigenetic aberrations in the development and progression of BD. Next, we focus on drug response-related alterations in the epigenetic landscape, including DNA methylation, histone modifications, and non-coding RNAs. Afterward, we delve into the potential roles of GM-induced epigenetic changes in the pathogenesis of BD and GM-based therapeutic strategies aimed at improving BD outcomes through epigenetic modifications. We also discuss how BD drugs may exert beneficial effects through modulation of the GM and the epigenome. Finally, we consider future research strategies that could address existing challenges.